2012
DOI: 10.1051/mmnp/20127304
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling Framework For Immune-related Diseases

Abstract: Abstract. About twenty five years ago the first discrete mathematical model of the immune system was proposed. It was very simple and stylized. Later, many other computational models have been proposed each one adding a certain level of sophistication and detail to the description of the system. One of these, the Celada-Seiden model published back in 1992, was already mature at its birth, setting apart from the topic-specific nature of the other models. This one was not just a model but rather a framework with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Parameter values are shown in Table 1 and have been set at reasonable values based on results coming from the literature, from the observation of the in vivo experiments and from our past experience (Castiglione et al, 2012;Halling-Brown et al, 2010;Pappalardo et al, 2006Pappalardo et al, , 2009aPappalardo et al, , b, 2010Pappalardo et al, , 2011Pappalardo et al, , 2012Pennisi et al, 2008Pennisi et al, , 2009.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Parameter values are shown in Table 1 and have been set at reasonable values based on results coming from the literature, from the observation of the in vivo experiments and from our past experience (Castiglione et al, 2012;Halling-Brown et al, 2010;Pappalardo et al, 2006Pappalardo et al, , 2009aPappalardo et al, , b, 2010Pappalardo et al, , 2011Pappalardo et al, , 2012Pennisi et al, 2008Pennisi et al, , 2009.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In this paper, we also suggested that ABMs are more suitable for modelling of different infectious diseases. ABMs of diseases help scientists to figure out the mechanisms of the immune system to validate hypotheses and to develop new medicines that are able to restrain certain diseases [39]. As with all simulation methods, ABM approach has certain limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Temporally, the authors modelled whole HIV infection that lasts for several years, and spatially they simulated individual cells of the lymphatic tissues. The importance of C‐ImmSim and its applicability to different diseases such as infectious diseases, allergies, and atherosclerosis are delineated in [39].…”
Section: Immune System Modelling Using Agent‐based Modelling Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Living organisms are natural complex systems and modeling may play a crucial role since models can also be built with approximate and imperfect knowledge of the phenomenon, and model parameters (initial data, entities, relations between entities) can be adjusted to fit modeling results to experimental measurements [1]. …”
Section: Introductionmentioning
confidence: 99%